2021
DOI: 10.1186/s42234-021-00075-7
|View full text |Cite
|
Sign up to set email alerts
|

A method to quantify autonomic nervous system function in healthy, able-bodied individuals

Abstract: Background The autonomic nervous system (ANS) maintains physiological homeostasis in various organ systems via parasympathetic and sympathetic branches. ANS function is altered in common diffuse and focal conditions and heralds the beginning of environmental and disease stresses. Reliable, sensitive, and quantitative biomarkers, first defined in healthy participants, could discriminate among clinically useful changes in ANS function. This framework combines controlled autonomic testing with fea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 130 publications
(114 reference statements)
0
14
0
Order By: Relevance
“…Additionally, a significant increase in pupillary unrest index, and a significant decrease in sample entropy, was found during the deep breathing condition [65]. However, in an investigation into the physiological responses to a series of autonomic function tests, which included a 7-min period of deep breathing at 6 bpm, no significant changes in pupil diameters were discovered [15].…”
Section: Breathing Depthmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, a significant increase in pupillary unrest index, and a significant decrease in sample entropy, was found during the deep breathing condition [65]. However, in an investigation into the physiological responses to a series of autonomic function tests, which included a 7-min period of deep breathing at 6 bpm, no significant changes in pupil diameters were discovered [15].…”
Section: Breathing Depthmentioning
confidence: 95%
“…Six studies included in this review reported results for measures of breathing depth, volume, or amplitude [15,21,36,50,59,65].…”
Section: Breathing Depthmentioning
confidence: 99%
“…Neural interfaces used for stimulation can also be used to record neural signals and monitor ANS activity in real-time ( 13 ). While innovative neural interfaces with multiple contacts are designed to improve the quality and information content of neural recordings ( 148 151 ), comparable efforts are being made to develop advanced signal processing and data analysis methods ( 152 , 153 ).…”
Section: Vagus Nerve Stimulation For Cardiovascular Diseasesmentioning
confidence: 99%
“…The development of BM was inspired by the growing comprehension of the autonomic nervous system (ANS), which plays a key role in the control of whole-body homeostasis. Dysfunctions of the ANS are consequently implicated in the development and progression of many diseases, including those affecting the cardiovascular system ( 4 , 7 13 ). BM utilizes this body of knowledge as a reference for the design of implantable devices ( 5 ) that modulate signals of the peripheral nervous system to visceral organs for therapeutic purposes ( 14 – 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of them require specialized equipment and trained staff to perform the evaluation. Parasympathetic responses decrease with increasing body mass index (BMI) [ 5 ]. Recently, a considerable amount of attention has been paid to hematological parameters as an innovative tool to evaluate a variety of ASN alterations related to an acute coronary syndrome in the hospital setting.…”
Section: Introductionmentioning
confidence: 99%